KKN-M Pendampingan Belajar dari Rumah pada Masa Pandemi Covid-19 untuk Anak SD di Desa Bamo Kecamatan Kota Komba Kabupaten Manggarai Timur - Maria Angelina Gua; Elfrida Yosefina Marlon; Adrianus Nasar (Prima Abdika : Jurnal Pengabdian Masyarakat, 2021)
Community service activities were carried out in Bamo Village, Kota Komba District, East Manggarai Regency. The purpose of this community service activity was to conduct tutoring assistance activities for elementary school students during the Covid-19 pandemic. Where tutoring activities were carried out by gathering elementary school students in one house. The implementation of independent KKN by Flores University students is carried out in three stages, namely introduction, implementation of activities and results of activities. The implementation of KKN is focused on a special theme, namely Innovation and Elementary Learning Technology. Learning innovation activities are carried out by utilizing technology tools in the form of a laptop. Where the laptop functions to play animated videos. And the results of the activities are documented in the form of videos and photos. The results of this learning innovation activity are where SDK Waepoang students are increasingly interested in participating in tutoring activities.